Kelekatan Anak di Panti Asuhan dan Pondok Pesantren Muhammadiyah Gurah Kabupaten Kediri - Darwati, Yuli (Happiness: Journal of Psychology and Islamic Science, 2023)
The purpose of this study was to find out: 1) Attachment of orphanage children to caregivers at the Muhammadiyah Islamic Bording school and Orohanage; 2) The attachment style of the children at the Muhammadiyah Gurah Islamic Boarding School and Orphanage in, is it secure, avoidant, or anxiety; 3) the factors that influence the attachment style. This research uses a qualitative descriptive research framework with a case study model. Data collection was carried out by observation and interviews with both orphanage children and caregivers, as well as documentation. The research subjects were 5 children living in the Muhammadiyah Gurah Islamic Boarding School and orphanage. Checking the validity of the data was carried out by extending participation and triangulation. The results showed: a) 2 out of 5 subjects had an attachment to their caregivers and the remaining 3 subjects had no attachment to their caregivers; b) three of the study subjects developed a secure attachment style. The remaining 2 subjects developed an insecure (anxious) attachment style; c) Factors that influence the development of attachment style: the role of caregivers, age at the orphanage, parental social support, and self-acceptance.